The Effects of Carbon Tax, Fairness, and Government Trust on Public Views of Carbon Tax - Adhityawati Kusumawardhani; Vanessa Saptadjaja; Megan Cahyono (Universitas Trunojoyo Madura, 2024)
The research aim to investigate the impact of fairness, trust, and carbon taxation on public perceptions of carbon tax. The purposive sampling procedure was employed to conduct this quantitative research. Indonesia’s primary contributor to carbon emissions is Java Island, which accounts for approximately 60% of the nation’s total emissions. The survey was administered online to 200 residents of the island. The populix/poplite platform was employed to draw the sample. SPSS was employed to perform multiple regression analysis. The findings of this investigation indicate that the public’s perceptions of Java are substantially influenced by fairness, trust, and carbon taxes. These findings indicate that the public is of the opinion that the carbon tax will be applied equitably and will have a positive impact on the environment. This research bolsters the public of view theory, which is crucial for the government to comprehend the critical factors that influence public acceptance and support for policy measures aimed at achieving sustainable objectives in the context of environmental policy. Additionally, it contributes to a more profound comprehension of the dynamics of public opinion in the context of climate change.